Utopia in ‘realistic’ theory of representative democracy and realism in ‘utopian’ theories of deliberative and participatory democracy - Klimowicz, Katarzyna (Hybris, 2016)
While many people all over the world become conscious about serious defects and inefficiencies of the prevailing political systems based on representative democracy, alternative solutions for more just and inclusive systems of governance continue developing. Alternative forms of democracy based on the idea of civic participation and deliberation have more and more followers, who are willing to implement innovative participatory and collective decision making practices in various areas and at various organizational levels. However, the strife for greater self-governance, reinforcement of citizens role in political decision-making processes and establishment of bottom-up control over public expenditures is often considered as a merely utopian project, especially by those who benefit most from the current status quo. In this article, I examine the fundamental ideological challenges for the new egalitarian approaches and argue that instead of making dichotomous distinction between utopianism and realism, realistically utopian approach is the most desirable.